Bathymetric, latitudinal and vertical distribution of protozooplankton in a cold-temperate shelf (southern Patagonian waters) during winter - Santoferrara, L.F. (2011)
Although there have been many ecological field studies on the key components of planktonic food webs, there are still gaps in knowledge on some groups, environments and seasons. This is the first report on the spatial distribution of the density and biomass of almost all the taxonomic groups and size fractions of protozooplankton across a cold-temperate shelf during winter. Twenty-eight stations (two or three depths) were sampled on four cross-shelf transects in Patagonian waters (south-western Atlantic; 47-55°S, 60-69°W) during September 2006. Loricate ciliates, radiolarians and foraminiferans showed the lowest densities, and were distributed mainly in coastal, slope or the whole shelf waters, respectively. The density and biomass of aloricate ciliates and heterotrophic nanoflagellates and dinoflagellates were low and homogeneous both vertically and across the shelf south of 51°S, but peaked in the upper 40 m in offshore waters at 47°S. Microplanktonic aloricate ciliates, which represented 53% of the total protozooplankton biomass, reached values as high as 16 μg CL-1 on the last transect. Consequently, both protozooplankton biomass and its ratio to chlorophyll a concentration were significantly higher in the northern offshore waters. These trends were linked to higher subsurface temperature and chlorophyll a concentration, and lower copepod nauplii biomass. Our results probably reflect changes in both the availability of food resources and predators and the physical structure of the water column, which are a consequence of the different environmental conditions that coexist over the large latitudinal and longitudinal gradients covered during late winter. © The Author 2010.